Refórmese el art. 72 de la Ley Orgánica De Defensa Del Consumidor, respecto a las sanciones a la publicidad engañosa por los proveedores, en garantía del consumidor en el Ecuador - Ricalde Flores, Danilo Alejandro (2016)
The lack of advertising self-regulation in all the advertising business community and implementers of advertising. In the first chapter, we mentioned in the advertising self-regulation, a number of non-governmental institutions or private associations that provide advertising services that create self-regulation for the practice of advertising; regulations that are of particular character that limit the development of advertising in the field of business, marketing, advertising agencies, media and telecommunications, establishing forms of behavior and practice of advertising, advertising regulated by the same perpetrators. So, self limited by rules of behavior ethical codes of advertising to not counteract the faint line of licit advertising and unlawful and misleading advertising, in our Ecuadorian advertising medium there are no rules of advertising self-regulation or codes ethical companies that live off advertising in this or have their business. Often the suppliers of goods and services comply with advertising character, pseudo client services departments, and few of them are true showcases claim violated the rights of consumers. Nor they have worried about developing a policy of self guilds or associations of advertising companies, showing little interest in it, without any to this date projects forming ethical advertising standards and their willingness to implement it. There is no effective support to promote consumer protection and worse in advertising fields